Developing and Promoting a Spiritual Package Tour in the Mekong Delta at Non Nuoc Viet Trade & Service Travel Company Limited - Phung, Thi Hoang Uyen (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Major in Digital Travel and Tourism Services Management